Empowering Women in Using Spice Plants to Make Traditional Drinks in Sei Buluh Village Serdang Bedagai Regency - Rosramadhana Rosramadhana; Sudirman Sudirman; Muhammad Takwin Machmud; Magdalena NW. Manalu; Intan YN. Bakara; Erino Nainggolan (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Sei Buluh Village consists of 10 hamlets with a population of 11,454 people (5,801 men and 5,653 women). Residential area 600 Ha, moorland 60 Ha. Around 82 percent of the land in Sei Buluh Village is designated as rice fields and fields. It can be concluded that the superior potential possessed by Sei Buluh Village is agriculture. In this case, problems were found in the utilization of agricultural and plantation products, while education and economic levels were still low. The solution to partner problems is to empower housewives by reviving home industries through processing spice plants. The impact is expected to be an increase in family income. This effort is also carried out for inheritance and economic improvement through empowering women, especially housewives. This is to achieve equal development that upholds the honor and dignity of a just nation. Methods for implementing activities include planning, organization, actualization and supervision. The implementation stages are: (1) survey and analysis of target groups by conducting site inspections; (2) identifying program needs by refining the concepts that have been formulated; (3) preparation of facilities and infrastructure; (4) implementing the program by providing socialization and practice of making traditional drinks; (5) evaluation. The results of the activity provide increased knowledge for housewives as target partners, regarding the use of agricultural products as traditional spice drinks, including digital technology-based packaging and marketing techniques.